Apolipoprotein E epsilon 4 allele frequency in patients with Lewy body dementia, Alzheimer's disease and age-matched controls. - St Clair, D; Norrman, J; Perry, R; Yates, C; Wilcock, G; Brookes, A (1994)
Genotypes of apolipoprotein E (ApoE) were determined by polymerase-chain reaction (PCR) amplification and restriction-sizing of brain DNA from 39 cases of Lewy body dementia (LBD), 68 senile Alzheimer's disease (AD) patients and 47 neuropathologically validated non-demented controls. There was a 3-fold increase in the epsilon 4 allele frequency in both LBD and AD groups compared with controls. These results indicate that LBD and AD share the epsilon 4 allele of ApoE as a major risk factor for the development of disease and suggest a similarity in disease aetiology.